Friedrich Weickmann (1913–1983): Some Reminiscences - Nisch, Gunther; Collmann, Hartmut (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Friedrich Weickmann was one of the most distinguished neurosurgeons of the former German Democratic Republic and an eminent representative of the neurosurgical school established by Fedor Krause. For 25 years he was head of the neurosurgical department in Berlin-Buch, which he developed into an excellent nonuniversity center. Weickmann was the first German to publish a comprehensive text on pediatric neurosurgery. He deserves particular credit for defending the autonomy of the neurosurgical specialty and for promoting neuroradiology as a subspecialty of radiology.
Keywords: Weickmann; neurosurgery; history; German Democratic Republic; Berlin-Buch